Combo-743: a new variety of Kabuli-type chickpea for producing areas of the northwest and El Bajío - Valenzuela-Herrera, Víctor; Cota-Barreras, Carlos Iván; Padilla-Valenzuela, Isidoro; Acosta-Gallegos, Jorge Alberto; López-Guzmán, Jesús Asunción; Ramírez-Soto, Milagros (Revista Mexicana de Ciencias Agrícolas, 2024)
Mexico is the twelfth largest chickpea producer worldwide. The production of Kabuli-type chickpea is located in the states of Sinaloa, Michoacán, Sonora, Guanajuato, and Baja California Sur, where grain of high caliber is obtained, which has made the Mexican chickpea famous worldwide. The new Kabuli-type chickpea variety, ‘Combo-743’, was derived from the cross between from two commercial varieties, Progreso-95 × Blanco Sinaloa-92. The Combo-743 variety adapts to all chickpea production areas in Mexico; the plant is semi-erect, the flower is white, its pod is medium in size, and its grain is creamy white with pronounced roughness, similar to that of Blanco Sinaloa-92. This new variety is resistant to the wilting disease caused by Fusarium species. On average of five trials, Combo-743 yielded 2 317 kg ha-1 compared to 2 146 kg ha-1 of Blanco Sinaloa-92 (the commercial variety with the largest sown area). Combo-743 has a caliber of 43 grains/30 g and an export percentage of 94% (grains> 9 mm) compared to 91% of Blanco Sinaloa-92.